The Effect of Training Apparatus for Improving Explosive Ability and Working Muscles Flexibility in Female Hammer Throwing Rotation Phase - Raheem, Fatima; Shaghati, Ahlam (Journal of Physical Education, 2020)
The problem of the research lies in weakness in physical abilities, especially explosive ability and working muscle flexibility during the rotation phase as well as the lack of modern styles and apparatuses used for training. The importance of the research lies in developing explosive power and working muscle flexibility during rotation using a proposed training apparatuses. The research aimed at designing a proposed apparatus and designing exercises for developing explosive power and flexibility. The researchers used the experimental method on (5) female hammer throwers. The researchers concluded that these exercises positively affected explosive power of arms and legs and flexibility of trunk, shoulder, back in subjects understudy.